CORRECTION OF FACIAL ASYMMETRY ASSOCIATED WITH UNILATERAL HYPOPLASTIC MANDIBLE WITH MONOBLOC DISTRACTION OSTEOGENESIS IN ADULT: Correction of Facial Asymmetry - Liaqat, Sehrish; Bukhari, Syed Gulzar Ali; Ahmed, Waseem; Qayum, Muhammad Umar; Ehsan, Afeefa; Khan, Hamid Ali (Pakistan Armed Forces Medical Journal, 2014)
Facial asymmetry can be corrected by bimaxillary orthognathic surgery and distraction osteogenesis. We report a case of facial asymmetry which was corrected using monobloc distraction osteogenesis. A monobloc was created using an osteosynthesis fixation device from the zygomatic buttress to the mandible, LeFort I osteotomy was combined with mandibular angle osteotomy and the bloc was distracted using uni-directional distractor.